2018
DOI: 10.1002/lary.27302
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Postoperative Therapy for Salivary Gland Adenoid Cystic Carcinomas

Abstract: 2c. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 37 publications
(110 reference statements)
1
26
0
Order By: Relevance
“…Prior studies evaluating cohorts of parotid cancer or mixed major and minor salivary malignancies reported decreased OS with positive margins. 22-25,29,47 However, this was not confirmed in studies restricted to submandibular carcinoma, likely due to low power. Cohen et al 20 evaluated 22 patients with submandibular adenoid cystic carcinoma and found that OS did not differ by margin status.…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies evaluating cohorts of parotid cancer or mixed major and minor salivary malignancies reported decreased OS with positive margins. 22-25,29,47 However, this was not confirmed in studies restricted to submandibular carcinoma, likely due to low power. Cohen et al 20 evaluated 22 patients with submandibular adenoid cystic carcinoma and found that OS did not differ by margin status.…”
Section: Discussionmentioning
confidence: 95%
“…The adenoid cystic carcinoma is a severe disease, which is featured by the resistance to various treatments such as chemotherapy (i.e., see Visa et al 2010; Caballero et al 2013; Cassidy et al 2018) including metronomic therapy. Given this fact we decided to investigate the transcriptional profiles of ACC samples and compare them with transcript profiles of normal tissue to identify the molecular features which could be helpful in the explanation of such severe chemoresistancy of ACC.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery with postoperative radiotherapy remains the most effective therapeutic modality in patients with early-stage head and neck adenoid cystic carcinoma (Coca-Pelaz et al 2015 ). In the case when surgery is impossible, the radiotherapy has been used and some attempts with chemotherapy including metronomic therapy; however, the outcome of such treatments is not satisfactory (Visa et al 2010 ; Caballero et al 2013 ; Ko et al 2016 ; Cassidy et al 2018 ). As there is no efficient therapy for the advanced stage of the adenoid cystic carcinoma there was an urgent need to investigate molecular basis of this type of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 11 In contrast, some studies have found that no significant association exists between postoperative radiotherapy and OS. 9 , 12 At present, there are still limited data to guide doctors in choosing treatment during the postoperative period, and the clinical significance of adjuvant radiotherapy is still worthy of exploration. The present study is intended to examine the significance of adjuvant radiotherapy for the survival of ACC patients undergoing radical resection.…”
Section: Introductionmentioning
confidence: 99%